Ayurveda in dental practice and its role in the management of dental diseases: A narrative review - Rajendran, Poornima; R, Rajesh; J, Srihari; Chithresan, Koshy (Indian Journal of Integrative Medicine, 2023)
Nowadays, there are more and more common diseases that can be a severe health risk, add to the financial load, and lower people's quality of life. Due to the fact that oral disorders can be mainly avoided by following Ayurvedic regimens, the integrative science of Ayurveda has recently attracted attention on a global scale. Natural phytochemicals that have been extracted from plants and employed in traditional medicine are still being sought after as alternatives to manufactured chemicals. During hundreds to thousands of years of use, the botanicals used in the Ayurveda material medicine have been shown to be secure and efficient. The investigation of plants used in conventional medicine could result in the creation of fresh preventive or therapeutic approaches to oral health. Techniques for maintaining dental hygiene according to Ayurveda are secure, efficient, affordable, simple to use, typically free of adverse effects, and have long-lasting effects. These are self-care techniques that are simple to use at home. The current literature review focuses on the use of several ayurvedic medicines to treat dental disorders.